1991
DOI: 10.1046/j.1468-2982.1991.1105223.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Clinical Comparisons Between Common and Classical Migraine: A Questionnaire-Based Study

Abstract: In a questionnaire-based study we compared the clinical features of migraine with aura (classical migraine) and migraine without aura (common migraine) in 354 and 397 patients, respectively, attending The Princess Margaret Migraine Clinic. Other than those related to the aura, no significant differences were seen in any clinical features of the attack (e.g. frequency or duration of attacks, time of day at onset, location of headache at onset, severity of headache, or nausea and vomiting). Common migraine attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
4
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 19 publications
5
19
4
2
Order By: Relevance
“…Among women with menstrual triggers, migraines most commonly occur during the week before the onset of menses. 34,36,42,43 Migraines during menses are the next most frequent. Less frequent precipitants include lack of sleep, perfume or odors, and weather change.…”
Section: Migraine Precipitantsmentioning
confidence: 99%
“…Among women with menstrual triggers, migraines most commonly occur during the week before the onset of menses. 34,36,42,43 Migraines during menses are the next most frequent. Less frequent precipitants include lack of sleep, perfume or odors, and weather change.…”
Section: Migraine Precipitantsmentioning
confidence: 99%
“…Only McEwen and Stellar [3]mentioned it in their discussion of the concept ‘allostasis’ and its relevance for understanding biological stress responses and their relationship to disease. To the best of our knowledge, there have only been a few studies focusing specifically on weekend migraine [4, 5, 6, 7, 8, 9, 10]. Furthermore, other researchers have demonstrated that the incidences of stroke [11, 12]and myocardial infarction [13, 14]are higher on weekends than on workdays.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other researchers have demonstrated that the incidences of stroke [11, 12]and myocardial infarction [13, 14]are higher on weekends than on workdays. However, until now, more systematic knowledge of and insight into the possible underlying mechanisms has been lacking, except for some specific speculations regarding weekend migraine, which has been associated with a decrease in caffeine intake and the so-called ‘let-up’ phenomenon [5, 6, 7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Nos nossos casos a idade de início da ESA teve pico entre 10 e 19 anos, como frequentemente relatado na literatura [7][8][9][10] . Alguns autores, no entanto, encontraram este pico entre 20 e 29 anos 11,12 .…”
Section: Discussionunclassified
“…Nossos achados sobre os sintomas acompanhantes são similares aos da literatura 3,[7][8][9]11,[16][17][18] . Nós observamos que náusea, foto e fonofobia ocorrem na maioria dos ataques de enxaqueca, nos pacientes que têm estes sintomas.…”
Section: Discussionunclassified